Дослідження накопичення аскорбінової кислоти у рослинній сировині Thymus tauricus Klok. et Shost - Фуклева, Лариса Анатоліївна; Fukleva, L. A. (My University, 2021)
У роботі представлені дослідження якісного та кількісного вмісту аскорбінової кислоти у траві Th. tauricus Klok. et Shost., методом тонкошарової хроматографії та об'ємним титруванням. Що необхідно враховувати при стандартизації рослинної сировини та розробці фітопрепаратів, як джерело природних антиоксидантів. Накопичення вітаміну С спостерігалось у вегетаційний період при масовій вегетації рослинної сировини чебрецю кримського, складало до 0,55 ± 0,03 %. The study of promising essential oil species of plants with pronounced antioxidant, antimicrobial, anti-inflammatory action is an urgent task of modern pharmacy for the expansion of phytopreparations and their introduction into medical practice. The study of the accumulation of ascorbic acid in the plant material of Th. tauricus Klok. et Shost. in different phases of the growing season is considered in order to expand the range of phytopreparations with antioxidant action. It is known that ascorbic acid is not synthesized in the human body, but gets together with food, beverages of plant origin. The object for our study was selected grass Thymus tauricus Klok. et Shost., harvested according to generally accepted methods, from different places of growth during the growing season (May-August). Drying of the grass was carried out in an oven at t = 35 ° C, located in a thin layer up to 3 cm The presence of ascorbic acid was confirmed by thin layer chromatography, where white spots were observed on the orange field (Rf = 0.78). The titration method was used to quantify vitamin C in Crimean thyme herb. The obtained results indicated that the studied plant material Th. tauricus Klok. and Shost. contains significant concentrations of vitamin C, respectively, was up to 0.55 ± 0.03%, which must be taken into account when standardizing plant materials.
Investigation of ascorbic acid accumulation in plant raw materials Thymus tauricus Klok. et Shost
Keywords: аскорбінова кислота; чебрець кримський; тонкошарова хроматографія; ефіроолійна рослинна сировина; ascorbic acid; Th. tauricus Klok. and Shost; chromatography; essential oil vegetable raw materials